Influence of Polymer Coatings on the Mechanical Properties of Steel Samples in Tensile and Bending Tests - Pashkov, O.A. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: An experimental and theoretical study of the effect of polymer coatings on an epoxy-polyester base on the mechanical properties of samples in the form of steel plates has been carried out. It is shown that, despite the fact that the thickness of the coatings is only 100 μm, they have a significant effect on the mechanical properties of plates up to 1,5 mm thick, leading to a decrease in Young's modulus, tensile strength and ultimate deformations of the samples. It was shown that the elastic modulus of the coated plate cannot be determined unambiguously from tests for central tension and three-point bending. In bending tests, there is a more significant reduction in plate stiffness compared to tensile tests. This effect is confirmed by calculations within the framework of classical models of the theory of elasticity.